2019
DOI: 10.21475/ajcs.19.13.07.p1148
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ethanol preconditioning as a rapid seed vigour and viability test

Abstract: It is essential that tests for evaluating seed vigour be faster and increasingly efficient to enable precise differentiation among batches. In this way, it is possible to evaluate the quality of seeds based on the anaerobic metabolism of cells when exposed to environments lacking oxygen. Thus, the objective of this study was to establish methodology for evaluating the viability and vigour of 3 lots of cowpea (Amendoim cultivar) seeds using the ethanol test. The treatments were carried out in a completely rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…As such, emission increases in the direction of more degraded lots, converging with the decline in vigor detected by said tests. In fact, a relationship between ethanol production and seed deterioration has also been reported for melon (Ornellas et al, 2020), and caupi bean (Cavalcante et al, 2019), demonstrating that ethanol is a deterioration biomarker (Colville et al, 2012). Its production results from mitochondrial cell loss (Buckley and Huang, 2011), here resulting from damage accumulated during aging and the consequent production of metabolic energy through alcoholic fermentation by converting pyruvate into ethanol (Benamar et al, 2003;Ornellas et al, 2020).…”
Section: Resultsmentioning
confidence: 89%
“…As such, emission increases in the direction of more degraded lots, converging with the decline in vigor detected by said tests. In fact, a relationship between ethanol production and seed deterioration has also been reported for melon (Ornellas et al, 2020), and caupi bean (Cavalcante et al, 2019), demonstrating that ethanol is a deterioration biomarker (Colville et al, 2012). Its production results from mitochondrial cell loss (Buckley and Huang, 2011), here resulting from damage accumulated during aging and the consequent production of metabolic energy through alcoholic fermentation by converting pyruvate into ethanol (Benamar et al, 2003;Ornellas et al, 2020).…”
Section: Resultsmentioning
confidence: 89%
“…Based on the results (Figure 4), it is possible to state that the MQ-3 sensor could be used as a tool to control fermentation in soybean seeds, as a future vigor test. In tests that assess the amount of ethanol released by seeds, such as those conducted by Buckley & Buckley (2009) in canola seeds, Kodde et al (2012) in cabbage seeds, Onwimol et al (2019) in corn, and Cavalcante et al (2019) in beans, the authors used an adapted ethylometer, specific for humans, and reported problems with the equipment at some moments of the analyses. It is worth noting that the ethylometer identifies, through a quick and adequate analysis of the air expelled from the lungs, the presence and quantity of alcohol in the body, providing results equivalent to the values found in alveolar air.…”
Section: Resultsmentioning
confidence: 99%
“…MQ-3 semiconductor sensor for ethanol A completely randomized design was used for the ethanol measurements, to determine the stabilization time of the sensor, with five replicates of 25 visibly intact soybean seeds from each batch. The seeds were selected manually and placed in glass jars with a known volume (150 mL), containing 40 mL of distilled water (simulation of an anaerobic environment) (Cavalcante et al, 2019), and then submitted to a 2 hours rest period at a controlled temperature of 41 °C (Cavalcante et al, 2019). After this hydration period, the vials containing the seeds were carefully coupled to the other vials containing the MQ-3 sensor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine repetitions of 25 visually classified bean seeds were chosen for the ethanol measurements, which did not present apparent physical damage. First, each sample was individually placed in glass bottles of known volume (150 mL) and sealed with systems in their cap, then a volume of 70 mL of distilled water was added, which was enough to keep the seeds covered and in anoxia (Cavalcante et al, 2019), to simulate an anaerobic, anoxic environment, going through a resting period of 24 hours, which was the minimum safe time for ethanol production to occur (Cavalcante et al, 2019) at room temperature around 25°C. After this soaking period, measurements were taken with the sensor.…”
Section: Methodsmentioning
confidence: 99%